2018
DOI: 10.1021/acs.orglett.8b01577
|View full text |Cite
|
Sign up to set email alerts
|

Radical-Cascade Avenue for 3,4-Fused-Ring-Substituted Thiophenes

Abstract: A single-step intramolecular radical cascade reaction of diynes and thioacetic acid in the presence of a catalytic amount of azobis(isobutyronitrile) as a radical initiator has been developed to synthesize thiophenes. This method allows easy and effective construction of a thiophene scaffold having 3,4-fused-ring substitution and unsubstituted 2,5-positions for further functionalization and polymerization. Using this method, derivatives of cyclopenta[ c]thiophene, 3,4-ethylenedioxythiophene, and thiophene-cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 35 publications
1
19
0
Order By: Relevance
“…From the analysis of Figure 1B,D,F, it shows that single electron would transfer from C atom of IM1 to S6 atom of IM3. According to Agrawal et al [ 18 ] and our computational results, it found that the radical intermediate IM8 could also be yielded in the process from IM5 toP via SN2 reaction in Scheme 4. So in the Path 2, radical IM8 reacts with CH 3 COSH to generate IM3 via transition state TS3.…”
Section: Resultssupporting
confidence: 53%
See 2 more Smart Citations
“…From the analysis of Figure 1B,D,F, it shows that single electron would transfer from C atom of IM1 to S6 atom of IM3. According to Agrawal et al [ 18 ] and our computational results, it found that the radical intermediate IM8 could also be yielded in the process from IM5 toP via SN2 reaction in Scheme 4. So in the Path 2, radical IM8 reacts with CH 3 COSH to generate IM3 via transition state TS3.…”
Section: Resultssupporting
confidence: 53%
“…Based on Agrawal et al, [ 18 ] thiolacetic acid (CH 3 COSH) would go through a Ssp 3 –H activation process, which could convert diyne into cyclopenta[ c ]thiophene and its derivatives in the solvent of toluene at the temperature of 80°C in Scheme 2. Firstly, AIBN initiator would go through a homolytic reaction to generate the radical IM1, which could convert CH 3 COSH into thiyl radical via two Ssp 3 –H activation paths; then diynes (R1, ···, R11) as the reactants could interact with thiyl radical to yield a series of products.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Pioneer work regarding the synthesis of different CPT and their application in OFETs has been reported later by Y. Aso et al . and Zade et al . In recent years, synthesis of 2,5‐disubstituted CPT from various substrates of diverse functionality was repoted by Yamamoto et al .…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, this is one of the few examples of a diyne cyclization via thiyl radicals that one can find in the literature. A second account of diyne reactivity under thiyl radical addition appeared three decades later, in which Agrawal et al optimized a number of substrates with malonate-type backbones for cyclization to the respective thiophene [35]. This approach relies on thermolysis of AIBN in toluene with thioacetic acid as the acyl thiyl radical source, and furnished a number of the bicyclic thiophenes, in good yield.…”
Section: Introductionmentioning
confidence: 99%